Bringing multiliteracies into process writing approach in ELT classroom: Implementation and reflection - Salim Nabhan (Universitas Islam Sultan Agung, 2019)
Designing new pedagogy in response to the advancement of technology that requires the integration of literacy has became the issue in ELT classroom. What is more, the conception of teaching English skills, including writing, is not merely limited to the language skills target but also how the learners become multiliterate in facing todays’ world. This article puts forward the framework of multiliteracies that is integrated in process writing approach to bridge the gap between literacy education and writing pedagogy. This study aims at investigating the enactment of the incorporation of multiliteracies with process writing approach and to explore the learners’ reflection toward the use of the framework in their writing practices. The data were taken from online surveys, the participants’ reflection, observation, and focus group discussion in the end of the study. Researcher used qualitative analysis with embedded quantitative data. The proposed framework was delivered to pre-service teachers (PST) in English Writing subject at the English Language Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, Indonesia. Step by step procedures in process writing approach were incorporated with multiliteracies along with some activities used in teaching writing. Findings indicated that implementing the framework in teaching writing provides PSTs with the opportunities to embrace the multiple modes of meaning making and digital technology in writing, produce texts, and present them in multimodal and creative ways. In addition, despite several challenges in its implementation, the activities helped to improve the writing skill, decrease the chance of plagiarism, and increase the authentic writing. Finally, PSTs were motivated to enhance their digital literacy used in writing practices. As a result, the study suggests that multiliteracies had a space in the teaching writing skill following the guided procedures in process writing approach.